S‐Doping Regulated Iron Spin States in Fe−N−C Single‐Atom Material for Enhanced Peroxidase‐Mimicking Activity at Neutral pH - Zhu, Fuying; Yu, YueYi; Yu, Zhixuan; Qiu, Haochen; Lu, Guo‐Ping; Chen, Zhong; Hu, Jun; Lin, Yamei (Small (Weinheim an der Bergstrasse, Germany), 2024)
Designing biomimetic nanomaterials with peroxidase (POD)‐like activity at neutral pH remains a significant challenge. An S‐doping strategy is developed to afford an iron single‐atom nanomaterial (Fe1@CN‐S) with high POD‐like activity under neutral conditions. To the best of knowledge, there is the first example on the achievement of excellent POD‐like activity under neutral conditions by regulating the active site structure. S‐doping not only promotes the dissociation of the N─H bond in 3,3″,5,5″‐tetramethylbenzidine (TMB), but also facilitates the desorption of OH* by the transformation of iron species’ spin states from middle‐spin (MS FeII) to low‐spin (LS FeII). Meanwhile, LS FeII sites typically have more unfilled d orbitals, thereby exhibiting stronger interactions with H2O2 than MS FeII, which can enhance POD‐like activity. Finally, a one‐pot visual detection of glucose at pH 7 is performed, demonstrating the best selectivity and sensitivity than previous reports. A N,S‐co‐doped iron single‐atom carbon material (Fe1@CN‐S) is synthesized to efficiently mimic peroxidase‐like activity under neutral conditions by regulating the spin state of iron species through sulfur doping, and it also accomplishes one‐pot colorimetric detection of glucose.